Correction to: The effect of New Zealand blackcurrant on sport performance and related biomarkers: a systematic review and meta-analysis - A. J. Braakhuis; V. X. Somerville; R. D. Hurst (Taylor & Francis Group, 2021)
An amendment to this paper has been published and can be accessed via the original article.